AUTHENTIC MATERIALS ENHANCE STUDENT’S WRITING ON DESCRIPTIVE TEXT - Abraham, Andi; Sutapa, Y. Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe objective of the research is to enhancing student?s writing skill on descriptive text through authentic material to the Grade Eighth Students of SMP Negeri 3 Samalantan. Moreover, this research to solve the student?s problem in learning writing descriptive text.  This research is a classroom action research using Kemmis and Taggrat procedure ; planning of action, implanting of action, observing and evaluation analysis and reflection. Triangulation approach administered as the technique of data analysis. The participants were students at the junior high school grade VIII of SMP N 3 Samalantan in academic year 2015/2016. The classroom action research conducted in three cycles, each cycle consists of two meeting. The result of the classroom action research obtained that the authentic material enhanced student?s ability in writing descriptive text. Authentic materials do not only increase the student?s achievement on writing descriptive text but also bring a joy full learning atmosphere. Moreover, the classroom activity became alife.      Key Word: Authentic Material, Writing Skill, And Descriptive Text